Extraordinary Sensitivity of Surface‐Enhanced Raman Spectroscopy of Molecules on MoS2 (WS2) Nanodomes/Graphene van der Waals Heterostructure Substrates. Issue 8 (10th February 2019) - Ghopry, Samar A.; Alamri, Mohammed A.; Goul, Ryan; Sakidja, Ridwan; Wu, Judy Z.
Abstract: Two‐dimensional transition metal dichalcogenides (TMDs)/graphene van der Waals (vdW) heterostructures integrate the superior light–solid interaction in TMDs and charge mobility in graphene, and therefore are promising for surface‐enhanced Raman spectroscopy (SERS). Herein, a novel TMD (MoS2 and WS2 ) nanodome/graphene vdW heterostructure SERS substrate, on which an extraordinary SERS sensitivity is achieved, is reported. Using fluorescent Rhodamine 6G (R6G) as probe molecules, the SERS sensitivity is in the range of 10 −11 to 10 −12 m on the TMD nanodomes/graphene vdW heterostructure substrates using 532 nm Raman excitation, which is comparable to the best sensitivity reported so far using plasmonic metal nanostructures/graphene SERS substrates, and is more than three orders of magnitude higher than that on single‐layer TMD and graphene substrates. Density functional theory simulation reveals enhanced electric dipole moments and dipole–dipole interaction at the TMD/graphene vdW interface, yielding an effective means to facilitate an external electrostatic perturbation on the graphene surface and charge transfer. This not only promotes chemical enhancement on SERS, but also enables electromagnetic enhancement of SERS through the excitation of localized surface plasmonic resonance on the TMD nanodomes. This TMD nanodome/graphene vdW heterostructure is therefore promising for commercial applications in high‐performance optoelectronics and sensing. Abstract : The superior light–solid interaction in transition metal dichalcogenides (TMDs) and charge mobility in graphene are integrated in TMD nanodomes/graphene van der Waals heterostructures as a surface‐enhanced Raman spectroscopy (SERS) substrate. A Rhodamine 6G SERS sensitivity of 5 × 10 ‐12 m is demonstrated on these substrates. This enhancement is similar to the localized surface plasmonic resonance enhancement by metallic nanoparticles.